Pandangan Masyarakat terhadap Tahun Duda dalam Penentuan Hajatan Pernikahan dalam Perspektif Hukum Syariah - Anni Hayatus Zulfa; Rosyida Rosyida; Bahrul Fawaid (Fakultas Hukum Universitas Wahid Hasyim, 2025)
The “tahun duda” tradition practiced in Pidodo Village, Karangtengah District, Demak Regency, is a social custom that restricts a widowed or divorced man from remarrying before the completion of one year after divorce or the death of his wife. This practice has no normative basis in the Qur’an, Hadith, or classical Islamic jurisprudence concerning marriage, thus raising questions regarding its legal status in Islamic law. This study aims to analyze the tradition from the perspectives of ‘urf and maqāṣid al-sharī‘ah. The research employs a normative legal method with conceptual and case approaches, relying primarily on library research supported by field data as social illustration. The findings indicate that the tahun duda tradition does not possess binding legal force in Islamic law. It may be categorized as valid ‘urf (ʿurf ṣaḥīḥ) if understood merely as a social ethic without theological implications. However, if it is believed to bring metaphysical consequences or positioned as a religious obligation, it potentially constitutes invalid ‘urf (ʿurf fāsid). Therefore, the tradition cannot be equated with Islamic legal provisions, and its legitimacy depends on how it is socially interpreted and practiced.